2013
DOI: 10.3892/mmr.2013.1433
|View full text |Cite
|
Sign up to set email alerts
|

BDNF protects retinal neurons from hyperglycemia through the TrkB/ERK/MAPK pathway

Abstract: Diabetic retinopathy (DR) is one of the most common diabetic eye diseases and a leading cause of blindness. It is characterized by changes in the blood vessels of the retina. The pathogenesis of DR is complex and to date, the precise mechanisms involved remain unclear. Previous studies have reported that DR is associated with neurodegeneration and that apoptosis may occur in diabetic retinas. In the present study, retinal neurons under conditions of hyperglycemia were used as a model to study apoptosis in diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 24 publications
0
36
0
2
Order By: Relevance
“…Numerous studies indicated that ERK1/2 and JUK could be activated by many environmental stressors or chemical agents via induction of oxidative stress, but this phenomenon was inhibited by treatment with antioxidants Geng et al, 2014;Wang et al, 2014;Zhang et al, 2012). Also, oxidative stress could increase the protein or mRNA levels of MAPKs (Biswas et al, 2012;Liu et al, 2012;Liu et al, 2013). Our study showed that exposure to nitrite increased the mRNA levels of JUK1, implying that the JUK signaling pathways likely played a role in the damage of the turbot gill or branchial cells after nitrite exposure.…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies indicated that ERK1/2 and JUK could be activated by many environmental stressors or chemical agents via induction of oxidative stress, but this phenomenon was inhibited by treatment with antioxidants Geng et al, 2014;Wang et al, 2014;Zhang et al, 2012). Also, oxidative stress could increase the protein or mRNA levels of MAPKs (Biswas et al, 2012;Liu et al, 2012;Liu et al, 2013). Our study showed that exposure to nitrite increased the mRNA levels of JUK1, implying that the JUK signaling pathways likely played a role in the damage of the turbot gill or branchial cells after nitrite exposure.…”
Section: Discussionmentioning
confidence: 95%
“…In the adult, BDNF expression that enhances and supports brain plasticity is increased by EE housing [45][47]. It was shown that serum and retinal levels of BDNF are significantly reduced at early stages of diabetes in rats [48], and BDNF protects retinal neurons from hyperglycemia in vitro [49], supporting that decreased BDNF levels may damage retinal cells early in the course of diabetes. In agreement, BDNF-immunoreactivity decreased in the retina from SE-housed diabetic animals as compared with non-diabetic animals, whereas EE housing prevented the effect of experimental diabetes on BDNF immunoreactivity.…”
Section: Discussionmentioning
confidence: 97%
“…Hyperglycemia could lead to the apoptosis of both retinal neurons and vascular cells [28,29]. RGCs are located in the inner retina, and are easily injured in response to high glucose stress.…”
Section: Discussionmentioning
confidence: 99%